The Effect of essential oil extracted from yellow peel of Citrus aurantium L. on growth of some fungi - Muhsen, Th. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The study was conducted to evaluate the effect of essential oil extracted from yellow peels of Citrus aurantium on the radial growth of all fungi.  Penicillium expansum, Aspergilus flavus and Fusarium oxysporum.              The results showed significant gradual reduction of the surface growth of fungi, P. expansum and A. flavus was more affected by the essential oil, while  F. oxysporum  showed less sensitivity towards the essential oil. The reaction of growth was inconcommitant with increasing concentrationsof oil, reaching concentration of (5)% which showed complete inhibition.